Effect of the pulling, crystal and crucible rotation rate on the thermal stress and the melt–crystal interface in the Czochralski growth of germanium crystals. Issue 39 (22nd September 2021) - Saadatirad, Mahboobeh; Tavakoli, Mohammad Hossein; Khodamoradi, Hossein; Masharian, Seyedeh Razieh
Abstract : The effect of the pulling rate on the melt–crystal interface shape and melt streamline is investigated. Abstract : A set of two-dimensional numerical simulations of the Czochralski growth of germanium crystals were performed in order to study the effect of the crystal pulling rate and crystal/crucible rotation rate on the flow and thermal field of the growth setup and the thermal stress within the grown crystal during different stages of the growth process. It was found that the crystal quality, which directly depends on the thermal stress distribution and the melt–crystal interface shape, is a result of the interaction of the considered growth factors. An approximately flat interface with minimum thermal stress in the grown Ge crystal can be achieved by the proper selection of these growth parameters.